Loss of anthocyanins and modification of the anthocyanin profiles ingrape berries of Malbec and Bonarda grown under high temperature conditions - de Rosas, María Inés; Ponce, María Teresa; Malovini, Emiliano Jesus; Deis, Leonor; Cavagnaro, Juan Bruno; Cavagnaro, Pablo (2018)
Malbec and Bonarda are the two most widely cultivated grape varieties in Argentina, and their derivedred wines are recognized worldwide, being their intense color a major quality trait. The temperature dur-ing fruit ripening conditions berries color intensity. In the main viticulture region of Malbec and Bonardaa 2–3◦C increase in temperature has been predicted for the upcoming years as consequence of the globalclimate change. In the present study, this predicted temperature raise was simulated under field-cropconditions, and its effect on anthocyanin pigmentation in berries of Malbec and Bonarda was monitoredby HPLC analysis throughout the ripening process, in two growing seasons. Additionally, expression lev-els of regulatory (MYBA1 and MYB4) and structural (UFGT and Vv3AT) anthocyanin genes were monitoredin Malbec berry skins. Although cultivar-dependent time-course variation was observed for total antho-cyanin content, in general, the berries of both cultivars grown under high temperature (HT) conditions hadsignificantly lower total anthocyanins (∼28–41% reduction), and a higher proportion of acylated antho-cyanins, than their respective controls. Expression of MYBA1 and UFGT, but not MYB4, was correlated withanthocyanin pigmentation at half ripening and harvest, whereas overexpression of the acyltransferasegene Vv3AT was associated with higher anthocyanin acylation in HT berries. These results suggest thatcolor development and pigment modifications in Malbec berries under HT are regulated at transcrip-tional level by MYBA1, UFGT, and Vv3AT genes. These data contribute to the general understanding on theeffect of high temperatures on anthocyanin biochemistry and genetic regulation, and may have directimplications in the production of high-quality wines from Malbec and Bonarda.